Efeito dos inibidores da xantina oxisidase em ratos submetidos à sepse induzida por LPS - Ramos, Maria Fatima de Paula [UNIFESP] (2017)
Objectives: To evaluate the effect of xanthine oxidase inhibitors in rats submitted to LPS administration. Material and Methods: LPS was administered i.p. (10 mg/Kg) every 24 hours until the 3rd day. XOi were given by gavage each 24 hour for 3 days. Allopurinol (Alo, 2 mg/kg) and febuxostat (Feb, 1 mg /kg) were used in an equivalent dose as in clinical use. To increase uric acid (UrAc) levels, Oxonic Acid (Oxo) was administered by gavage (750mg/Kg/day) during 5 days. UrAc measurements were done at baseline and at 6th day. The animals were divided into 10 groups (n = 6 each): 1-Control, 2-Alo, 3-Feb, 4-LPS, 5-LPSAlo, 6-LPSFeb, 7-Oxo, 8-OxoLPS, 9-OxoLPSAlo and 10-OxoLPSFeb. Data were evaluated by ANOVA and survival curves (Chi square) considering the value of p<0.05 for statistical significance. Data were reported as mean and standard deviation. Results: All animals that received LPS developed renal function impairment. Immuno histochemistry staining technique analysis in this groups, revealed less cellular proliferation evaluate by PCNA and increased apoptosis measured by cleaved caspase-3, compatible with severe sepsis. With simultaneous administration of Alo, in this experimental sepsis induced by LPS, a higher impact of septic shock was noted with significant increase in mortality rates (p<0.05) in the LPSAlo group (28/34; 82%) when compared with LPS group (10/16; 63%) and LPSFeb group (11/17; 65%). We noted lower mean values of creatinine clearance in the group who received only LPS (44%) (p<0.05); in the LPSAlo group (60%) (p<0.01) and in the LPSFeb group (35%)(p<0.05). Additionally, we obtained higher levels of reactive oxygen species (nMol/mg of creatinine in the 24-hour urine test, p<0.001) in the groups that received Alo, in LPSAlo group (293.3±35.8) and OxoLPSAlo group (304.3±60.4) compared with LPS group (267.8±44.9), LPSFeb group (220.0±39.1), OxoLPS group (236.7±33.2) and OxoLPSFeb group (211.2±43.6). In all the groups who received LPS, the levels of TNF-α increased about 3 times in relation to control groups in 17 hours and returned to basal levels in all groups, except in the LPSAlo and OxoLPSAlo groups where this late decline was not observed. We obtained significant superior values of IL-6 (pg/mL) in the groups that received Alo, LPSAlo group (238.8±28) (p<0.05) and OxoLPSAlo group (275.7±52) (p<0.01) compared with LPS group (175.7±40), LPSFeb group (199.5±23), but there was no statistically significant difference between the OxoLPS (231.3±19 pg/mL) e OxoLPSFeb (229.2±30 pg/mL) or LPSAlo vs OxoLPSAlo groups. After 72 hours, lower IL-6 values were present in about 50% of cases in all groups, except in LPSAlo and OxoLPSAlo groups were these values remained higher, both about 15 times in relation to the control group. Conclusion: In this study, simultaneous administration of Alo in the experimental sepsis induced by LPS enhanced the septic shock with increased in mortality, renal function impairment, high values for oxygen reactives species and for interleukins pro-inflammatory. Differently, when we administrate febuxostat, we do not observed potentiation in the septic situation, probably by higher selectivity and no interference in another metabolic event that probably occur with allopurinol.